The Correction of a Void Contract in Jurisprudence and Law of Iran - Mahdi Narimanpour; Mohammad Bahrami Khoshkar; Mohsen Esmaili (Faṣlnāmah-i Pizhūhish-i Huqūq-i Khuṣūṣī, 2022)
"Voidness" is a status on which no legal effect is exercised according to the law. Although this status is contrary to the rule in Islamic law, it has significant examples in Islamic law. An examination in jurisprudential and legal books shows that scholars of jurisprudence and law have tried to reduce the scope of this legal status and reduce its examples by creating institutions such as withdrawal of the contract, the principle of correctness and the theory of spiritual commonality. In this regard, according to the examples of correction of void contracts in Islamic law, we can reach a comprehensive and complete theory called "correction of void contracts", which on the one hand compared to similar comprehensive institutions and on the other hand It has far fewer problems than such institutions. Correction of a void contract means that a void contract is corrected by removing the invalid causes or changing and transforming the annulled elements of the contract.In this research, we intend to examine the aspects of this theory and to assess its validity in the balance of jurisprudence and law. The result shows that there is no serious problem in correcting a void contract from a jurisprudential and legal point of view, and this legal act can be considered as one of the legal theories along with other institutions limiting the scope of voidness.